Sanitary and phytosanitary measures in Chinese agricultural exports: the role of trade intermediaries. Issue 27 (9th June 2018) - Gibson, Mark J.; Wang, Qianqian
ABSTRACT: We study the effect of sanitary and phytosanitary (SPS) measures on Chinese agricultural exports and the role of trade intermediaries in this process following China's accession to the World Trade Organization. While both agricultural exports and SPS regulations have grown, the use of trade intermediaries has declined sharply. We develop a model of heterogeneous producer-level decisions about choice of export mode that is consistent with this trend. In our econometric analysis, we analyse the effects of SPS measures and trade intermediaries on Chinese fruit and vegetable exports using transaction-level customs data. In contrast to much of the literature, we find some evidence of positive relationships among SPS measures, trade intermediaries and exports.